Dielectric, impedance and modulus spectroscopy of Ta-based layered perovskite. (3rd July 2019) - Deepti, P. L.; Patri, S. K.; Choudhary, R. N. P.; Das, P.S.
ABSTRACT: PbBi2 Ta2 O9 ceramic samples were fabricated by high-temperature mixed oxide method. X-ray diffraction determines the structure as orthorhombic. The scanning electron microscopy confirms the formation of densely packed grains in the sample. The dielectric measurements, complex impedance and complex modulus study were carried out in a frequency range of 1 kHz–1 MHz and a temperature rangeof 25–500°C. The conduction mechanism of the material is discussed in details using variable range hoping, nearest neighbor hopping relaxation model and dc activation energy at two different temperature regimes. From the J-E characteristics studies, the occurrence of non-linear curves endorses the non-Ohmic nature of the material.